Buried ideas : legends of abdication and ideal government in early Chinese bamboo-slip manuscripts - Allan, Sarah (Albany : State University of New York Press, 2015)
"Four Warring States texts discovered during the late twentieth-century challenge longstanding understandings of Chinese intellectual history. The discovery of previously unknown philosophical texts from the Axial Age is revolutionizing our understanding of Chinese intellectual history. Buried Ideas presents and discusses four texts found on brush-written slips of bamboo and their seemingly unprecedented political philosophy. Written in the regional script of Chu during the Warring States period (475-221 BCE), all of the works discuss Yao's abdication to Shun and are related to but differ significantly from the core texts of the classical period, such as the Mencius and Zhuangzi. Notably, these works evince an unusually meritocratic stance, and two even advocate abdication over hereditary succession as a political ideal. Sarah Allan includes full English translations and her own modern-character editions of the four works examined: Tang Yú zhi dao, Zi Gao, Rongchengshi, and Bao xun. In addition, she provides an introduction to Chu-script bamboo-slip manuscripts and the complex issues inherent in deciphering them"--Publisher's website.
History and historical legend -- The Chu-script bamboo-slip manuscripts -- Advocating abdication : Tang Yú Zhi Dao, "The way of Tang Yao and Yú Shun" -- Tang Yú Zhi Dao : translation and Chinese edition -- The Zigao and the nature of early Confucianism -- Zigao : translation and Chinese edition -- Rongchengshi : abdication and utopian vision -- Rongchengshi : translation and Chinese edition -- The Bao Xun : obtaining the center to become king -- Bao Xun : translation and Chinese edition -- Afterthoughts.
Includes bibliographical references and index.
Print version record.
Texts written by and large in English, but occassionally in Chinese.
JSTOR
Keywords: China -- History -- Warring States, 403-221 B.C. -- Sources; China -- Politics and government -- To 221 B.C. -- Sources; China -- Kings and rulers -- Abdication -- History -- Sources; Ideals (Philosophy) -- Political aspects -- China -- History -- To 1500 -- Sources; Merit (Ethics) -- Political aspects -- China -- History -- To 1500 -- Sources; Political science -- China -- History -- To 1500 -- Sources; China -- Intellectual life -- To 221 B.C. -- Sources; Manuscripts, Chinese; Chinese language -- To 600 -- Texts; Chine -- Histoire -- 403-221 av. J.-C. (Royaumes combattants) -- Sources; Chine -- Politique et gouvernement -- Jusqu'à 221 av. J.-C. -- Sources; Chine -- Vie intellectuelle -- Jusqu'à 221 av. J.-C. -- Sources; Chinois (Langue) -- Jusqu'à 600 -- Textes; HISTORY -- Asia -- China; Chinese language; Intellectual life; Kings and rulers -- Abdication; Manuscripts, Chinese; Political science; Politics and government; China; Bambusinschrift; Herrschaftssystem; Ideal; Streitende Reiche; Politische Philosophie; Politisk filosofi -- historia; Kinesiska handskrifter; To 1500; History; Sources; Texts